The impact of age on clinical features and fertility outcomes in patients with polycystic ovary syndrome: a secondary analysis based on the PCOSAct trial - Lu, Fengjuan; Yu, Hong; Feng, Jiaxing; Liu, Yang; Ge, Hang; Shi, Baichao; Guan, Muxin; Ma, Hongli; Wang, Yu; Cong, Jing; Yang, Wen; Han, Conghui; et al. (Frontiers in Endocrinology, 2026)
ObjectiveThis study aimed to investigate age-related variations in baseline characteristics and reproductive outcomes among women with polycystic ovary syndrome (PCOS).MethodsA secondary analysis of the PCOSAct trial included 936 participants stratified into four age groups: 20–24, 25–29, 30–34, and 35–40 years. Differences in anthropometric measures, sex hormones, metabolic parameters, and pregnancy outcomes were analyzed using correlation and multiple logistic regression.ResultsWith increasing age, linear trends revealed increases in hirsutism score, systolic blood pressure, triglycerides, dyslipidemia, metabolic syndrome, and atherogenic indices (P-trend<0.05). Conversely, luteinizing hormone (LH), LH/FSH ratio, total testosterone, free testosterone, anti-Müllerian hormone (AMH), and HDL levels decreased (P-trend<0.05). Age independently correlated with these metabolic and endocrine shifts (all P<0.05). Advanced age was associated with higher ovulation induction success (adjusted OR = 1.058, 95% CI:1.006–1.114, P = 0.030) but also an increased risk of first-trimester threatened abortion (adjusted OR = 1.11, 95% CI:1.009–1.210, P = 0.031). No significant associations were observed with clinical pregnancy or live birth.ConclusionThe clinical presentation of PCOS evolves significantly with advancing age. It is typically characterized by a shift from a state of hyperandrogenism and reproductive abnormalities in younger women to a profile increasingly dominated by progressive metabolic disturbances and cardiovascular risks in later years. Although ovulation response improves in older patients, they face a higher risk of early pregnancy loss. This underscores the necessity of implementing age-stratified clinical management for individuals with PCOS.